Opportunities and challenges halal marketplace in Indonesia - Wahyu Setyorini; Ana Raudlatul Jannah; Uci Wulansari; Mir'atun Nisa (Journal of Halal Product and Research, 2021)
The development of information technology encourages the emergence of various online transaction activities, one of which is online trading transactions through the marketplace. Currently, Indonesia has the largest Muslim population, which is 87% of the total population who also takes part in buying and selling activities and online transactions. Muslim awareness and interest in halal products is increasing, but there is a need of understanding regarding transactions according to Sharia. The purpose of this study: to analyse the potential and challenges of the halal marketplace in Indonesia using a literature study research method. The results of this study indicate that in Indonesia the halal marketplace has a large market potential and is an innovation in the development of the existing marketplace. Besides this potential, the halal marketplace also has challenges in its development, including the low level of Islamic economic literacy among the public, low inclusion of Islamic finance, and the lack of utilization of the halal marketplace platform by halal MSMEs. It is hoped that these potentials and challenges can become views in determining and developing policies.